ASSESSMENT OF PESTICIDES RESIDUES IN FISH (Tilapi guineensi) in the Couffo River in Djidja (Benin) - AÏKPO, Firmin H.; AGBANDJI, Lucien; AHOUANSE, Miriac Dimitri S.; KOUMOLOU, Luc; HOUSSOU, CHRISTOPHE SÈGBÈ; EDORH, ALÉODJRODO EDGARD PATRICK VINCENT (My University, 2017)
In Benin, the main cash crop is the cotton of which the level of production is largely insufficient to satify the national and international market. The main food crops (corn, cassava, yam, bean, rice, etc.) permit to cover the food needed globally, but remain again extensively on this side of the potentialities offeres by the ecological conditions of the country. In te process to increase the agricultural production, the herbicides, insecticides ans the fertilizers are used now in higher quantity that in the past. The aim of this work was to assess the level of contamination of fish (Tilapi guineensis) in the Couffo River in Djidja (Benin) by the pesticides. Nine (09) samples of fish (Tilapia guineensis) have been collected in ninr (09) points along the Couffo River. The analysis of these fish has been done by gas chromatography after extraction and purification. In fish, the detected concentrations in average ranged between 0.123 µg/kg and 0.191 µg/kg for the glyphosate, from 0.095 to 0.128 µg/kg for the profenofos, between 0.112 µg/kg and 0.125 µg/kg for the acetamiprid and 0.127 and 0.139 µg/kg. To assess the risk to public health, pesticides intake by fish consumption was estimated and compared with Estimated Dailly Intake (EDI) valeus reported by the Codex Alimentarius. This comparaison showed that fish consumption does not pose a risk for public health.
Keywords: Pesticides; Djidja; cotton; fish; River